Efficacy of neoadjuvant chemotherapy with docetaxel and cisplatin in patients with squamous cell carcinoma of the oral cavity at high risk of progression - S. I. Kutukova; Yu. V. Ivaskova; N. P. Beliak; G. A. Raskin; A. A. Varankina; A. I. Yaremenko; A. Ya. Razumova; A. O. Cheremnykh; M. F. Manna; R. V. Orlova (Опухоли головы и шеи)
Introduction. The question of the advisability of neoadjuvant chemotherapy (NACT) in patients with oral cavity squamous cell carcinoma is still controversial.Aim. To identify a group of patients at high risk of progression and death from the oral cavity squamous cell carcinoma, with resectable stages, and to determine the effectiveness of docetaxel and cisplatin (TP) NACT patients with high-risk oral cavity squamous cell carcinoma.Materials and methods. At the 1st stage of our study, we retrospectively analyzed the data of 98 patients and determine that the NACT for patients with oral cavity squamous cell carcinoma, with 3 or more factors of an unfavorable prognosis (peripheral blood parameters indicating the presence of systemic inflammation, reduced level of infiltration of tumor structures by CD8‑tumor infiltrating lymphocytes and low expression of programmed death-ligand 1 (PD-L1) on tumor and immune cells) significantly reduces the risk of death and disease progression: hazard ratio 0.33; 95 % confidence interval 0.13–0.86; p = 0.0231. In 2nd part of study we assessed the effectiveness of 3 cycles of NACT with docetaxel + cisplatin in 24 patients with 4 or more unfavorable prognosis factors.Results. Objective response rate after 3 cycles of NACT was 66.7 % (16 / 24): 1 / 24 (4.2 %) patient had complete response, and 15 / 24 (62.5 %) patients had a partial response. NACT allowed achieving disease control rate in a significant majority of patients – 23 / 24 (95.9 %) (p <0.001). The medians of overall survival and progression-free survival weren’t reached at the time of the data cutoff (with a median follow-up of 56.5 months).Conclusion. Our study allows to conclude that it is necessary in real clinical practice to identify patients with oral cavity squamous cell carcinoma with high-risk of progression and death in order to prescribe them NACT before surgery to increase the effectiveness of treatment and reduce the risk of progression and.